Adjustment and Poverty in Mexican Agriculture : How Farmers' Wealth Affects Supply Response - Lopez, Ramon (The World Bank, 1999)
August 1995 - By and large, it appears that the goals of agricultural reform are being met in Mexico. But measures such as decoupling income supports and price supports or reorienting research and extension could help farmers who cannot afford access to machinery and purchased inputs and services. López, Nash, and Stanton report the results of a study of Mexican farm households using 1991 survey data and a smaller resurvey of some of the same households in 1993. One study goal was to empirically examine the relationship between assets and the output supply function. Using a production model focusing on capital as a productive input, they found that both the supply level and the responsiveness (elasticities) to changing input and output prices tend to depend on the farmer's net assets and on how productive assets are used. Regression analysis using data from the surveys shows that farmers who use productive assets such as machinery tend to be positively responsive to price changes, while those with no access to such assets are not. Another study goal was to monitor the condition of Mexican farmers in a rapidly changing policy environment. The 1991 survey data suggest that farmers with more limited use of capital inputs (the low-CI group) were more likely to grow principally corn and to grow fewer crops, on average, than the others. They also had more problems getting credit and were less likely to use purchased inputs, such as seeds, fertilizer, and pesticides, or to use a tractor to prepare the soil. They tended to be less well-educated, and their land tended to be of lower quality. Results from the panel data showed conditions generally improving for the average farmer in the sample area between 1991 and 1993, during a period when agricultural reforms were implemented.